A educação no jornal “O operário” (1909-1913): uma análise das tendências educativas - Tardelli Filho, Fábio Alexandre (2019)
This dissertation resulted from an exploratory investigation, initiated around 2015 and that had the objective of analyze the educational trends presents in the Sorocaba´s newspaper O Operário (1909-1913). The methodology used in this investigation was the documental type, based on the access to the facsimile that contains almost all the editions of the studied newspaper, and bibliographical, that occurred with the lecture of texts about the historical period which the newspaper was published, the educational trends and the commentators of the theoretical-methodological foundations they kept. The newspaper, primary font of this research, that was bi-weekly, had a publishing system based mainly on the collaboration of texts sent by various authors. Therefore, your pages reveal a wide range of discussions, oriented by diverse trends of theoretical-methodological paradigms, of the positivisms, which dealt especially about the sciences of nature and the religiosity, from the socialisms to the anarchisms. Although the themes were ample, with the research, related here, was possible to reach the expected result, that is, to identify and to analyze the proposals and debates about the educational trends presents in the newspaper.